Plasma radiation studies in Magnum-PSI using resistive bolometry. (26th July 2018) - van Eden, G.G.; Reinke, M.L.; Brons, S.; van der Bijl, G.; Krijger, B.; Lavrijsen, R.; Huber, S.P.; Perillo, R.; van de Sanden, M.C.M.; Morgan, T.W.
Abstract: Both the physics of divertor detachment and vapour shielding are characterized by a relatively large amount of radiation produced in the divertor. The linear plasma generator Magnum-PSI is well-suited to study such processes due to its ITER-divertor relevant plasma conditions, simplified geometry and diagnostic accessibility. The need the quantify the plasma radiated power close to the target surface motivated the development of a 4-channel resistive bolometer for Magnum-PSI, and marks the first deployment of such a diagnostic on a linear device. An axially resolved measurement of plasma emission at arbitrary distances from the target surface is now possible. The radial position of the detector can be varied, hereby viewing the full diameter of the plasma column or down to a central region. The overall system design is discussed alongside a comparison of the spectral absorbance of carbon-coated versus non-coated Au/Al bolometer sensors. Despite low electron temperatures of the plasma (1–5 eV), the observed power densities were found to be 10–37 times the sensor noise floor of  ̃0.1 W m −2 . A synthetic diagnostic based on collisional radiative model calculations from ADAS could well match observed values from H and Ne plasmas while the measured values for Ar and He were more difficult to reproduce. The obtained findings allow for approximate power balance calculations in Magnum-PSI indicating that maximally  ̃47% and  ̃14% of the total power is lost by radiation in the cases of Ar and Ne/He respectively. The results demonstrate the feasibility of resistive bolometry in low temperature high density plasma regions and on long timescales (>450 s) which is of relevance to ITER. Due to long-term temperature drifts which were observed, a recent upgrade involved the installation of a shutter and FPGA-based electronics for increased accuracy.